Jaw Dystonia and Reversible Basal Ganglia Changes as an Initial Presentation of Systemic Lupus Erythematosus. (January 2018) - Romba, Meghan; Wang, Yujie; Hu, Shu-Ching; Khot, Sandeep
Dystonia as a manifestation of neuropsychiatric lupus erythematosus (NPSLE) is uncommon. We report a 25-year-old woman who experienced progressive confusion, reduced speech, and difficulty opening her mouth approximately 2 weeks after development of a facial rash. Brain imaging showed bilateral, symmetric signal abnormalities within the basal ganglia and subcortical white matter. Despite treatment with high-dose steroids, she continued to have difficulty speaking with evidence of jaw dystonia on examination. Jaw dystonia rapidly improved with the initiation of levodopa. Repeat evaluation 3 months later exhibited the absence of jaw dystonia and near resolution of the imaging abnormalities. Our patient demonstrated a unique presentation with jaw dystonia refractory to traditional treatment for NPSLE. Such a presentation likely represents a severe variant of NPSLE requiring both immunosuppressive and symptomatic therapies.